Comparative economic analysis of borrwer and non-borrower Boro rice farmers in some selected sites of Mymensingh District - Sarkar, MSK; Hasan, MR; Feardous, MA; Shuhel, MMH; Moniruzzaman, M (Bangladesh Journal of Agricultural Research, 2010)
The present study has been conducted to examine the differences in input use, costs and returns of the borrower and non-borrower rice farmers. One hundred samples from four villages under Tiishal Upazila of Mymensingh district were selected for the study. The study reveals that borrower farmers used more inputs and attained more returns through higher yield than their counterparts. The yields of rice per hectare were 5260.80 kg and 4177.34 kg for the borrower and non-borrower farmers, respectively. The gross returns and net returns were Tk. 41699.03 and Tk. 4475.64, respectively, for the non-borrower farmers and Tk. 51589.53. and Tk. 8821.68, respectively, for borrower farmers. The undiscounted BCRs were 1.73 and 1.12 in case of non-borrower farmers and 1.74 and 1.21 for the borrower ones. The study further reveals that credit could be judged as a vital player to increase higher yield through utilization of necessary production inputs. Keywords: Borrower farmer; non-borrower farmer; cost and return. DOI: 10.3329/bjar.v35i1.5867 Bangladesh J. Agril. Res. 35(1) : 65-76, March 2010